Some uses, underuses, and misuses of the findings of disparities between people’s valuations of gains and losses - Knetsch, Jack L. (Applied Studies in Agribusiness and Commerce, 2016)
The well-known behavioural finding that losses have a greater impact on people’s well-being than gains, has important implications for the study of individual and collective choices, as well as the ways in which analyses are carried out -- many more than have yet been seriously considered. It also has many for analysts’ use of such tools as price elasticities, discount rates, value of statistical lives, risk analysis, and the like. A greater recognition of the behavioral findings would likely lead to reductions of the biases in many present analyses.